Primary Bone Marrow B-Cell Lymphoma Undetected by Multiple Imaging Modalities That Initially Presented with Hypercalcemia - Jin Sae Yoo; Juwon Kim; Hyeong Ju Kwon; Jung Soo Lim (Case Reports in Endocrinology)
Purpose. We report a rare case of severe hypercalcemia that was ultimately diagnosed as primary bone marrow diffuse large B-cell lymphoma (BCL). Case Report. A 74-year-old male patient visited our hospital complaining of tenderness and swelling of the left knee caused by supracondylar fracture of the left distal femur. His initial blood tests showed a serum calcium level of 13.9 mg/dL, inorganic phosphorus of 4.34 mg/dL, and a serum creatinine level of 1.54 mg/dL. A serum assay of intact parathyroid hormone showed 5.24 pg/mL, and the patient’s serum 25(OH)D level was 22.33 ng/mL. To exclude malignancy, we performed imaging studies, including abdomen or chest computed tomography and positron emission tomography-computed tomography; however, no suspicious lesion was found, although the serum PTH-related peptide level was elevated at 4.0 pmol/L. A bone marrow biopsy was performed to identify any hidden hematologic malignancy. As a result, the pathology of bone marrow confirmed the presence of atypical lymphocytes that stained positive for the CD20 marker, which is consistent with BCL involving the bone marrow. Conclusion. This case highlights the importance of pursuing a thorough workup for rare underlying causes of hypercalcemia when parathyroid-related etiologies can be excluded.